Thursday
March 23, 2017

Post a New Question

Posted by on Wednesday, October 3, 2012 at 3:34pm.

use the dissociation constant ka=[H+][A-]/[HA] to show that ph=pka

  • CHEMISTRY PH=PKA - , Wednesday, October 3, 2012 at 3:50pm

    pH = pKa ONLY when (A^-)/(HA) = 1
    Ka = (H^+)(A^-)/(HA). Rearrange to
    (H^+) = Ka*(HA)/(A^-).
    When (HA) = (A^-) then (HA)/(A^-) = 1 and
    (H^+) = Ka*1 or Ka.
    Take the negative log of both sides.
    -log(H^+) = -logKa
    -log(H^+) = pH and -logKa = pKa
    pH = pKa BUT that is true only when (HA) = (A^-)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question